Development of Learning Models to Enhance Students’ Creative Thinking: A Systematic Literature Review - Juliangkary, Eliska; Suparta, I Nengah; Ardana, I Made; Mahayukti, Gusti Ayu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
Creative thinking is an essential component in education that drives innovation, problem-solving, and the development of students’ critical thinking skills. This study aims to review various learning models designed to enhance students’ creative thinking abilities through a systematic literature review (SLR). Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, this research identifies, screens, and evaluates relevant articles from the Scopus database, resulting in eight studies that meet the inclusion criteria. The results indicate that, following innovative learning models such as play-based activities, digital-based virtual classrooms (VCLE), basic movement through play approaches, and project-based mathematics learning are effective in improving creativity, problem-solving, collaboration, and student learning motivation. The integration of technology, STEAM approaches, and creative game design also show positive effects in enhancing students’ creative thinking skills. The higher distribution of research at the tertiary education level highlights the need for greater focus on other educational levels, particularly secondary education, to ensure the benefits of learning innovation are evenly distributed. These findings provide practical implications for educators and policymakers, emphasizing the importance of using innovative teaching methods, integrated technology, and the role of teachers as facilitators to develop a conducive learning environment for student creativity. The study also identifies several limitations, including small trial scales and short research durations, indicating the need for further research with larger scales and longer durations. By continually exploring and developing effective learning models, it is expected that students can achieve their maximum potential in dynamic and diverse learning environments.